Neonatal renal vein thrombosis: Role of anticoagulation and thrombolysis—An institutional review. (2nd January 2016) - Bidadi, Behzad; Nageswara Rao, Amulya A.; Kaur, Dominder; Khan, Shakila P.; Rodriguez, Vilmarie
ABSTRACT: Neonatal renal vein thrombosis (NRVT) is a rare thromboembolic complication in the neonatal period, and sequelae from renal dysfunction can cause significant morbidity. The authors retrospectively reviewed 10 patients with NRVT treated at their institution. The majority of the cohort were male ( n = 9), preterm ( n = 6), and had unilateral NRVT ( n = 6). Six patients received thrombolysis and/or anticoagulation, and 4 patients received supportive care only. Two of the 6 patients treated with anticoagulation who had bilateral NRVT and anuria received thrombolysis with low-dose tissue plasminogen activator. Thrombolysis was not associated with any major adverse events, and both patients had marked improvement of renal function. Eight patients subsequently developed renal atrophy (3 received anticoagulation, 2 received thrombolysis with anticoagulation, and 3 received supportive care). Anticoagulation/thrombolysis did not appear to prevent renal atrophy. The role of thrombolysis needs to be further studied and considered in the setting of bilateral NRVT and acute renal failure.